GROUNDING ISLAMIC COMMUNICATION IN THE KORAN - Wibowo, Hendro (Proceeding International Seminar of Islamic Studies, 2023)
The family in the Qur'an is defined as a collection of men and women who are bound by marriage and in which there are people who are their dependents, such as children and in-laws. The family has a very strategic role and a very useful function. These roles are as a protector, educator of family members, liaison in the community, meeting their economic needs, fostering religious life, organizing family recreation and creating a safe and comfortable atmosphere for all family members and especially for husband and wife, as a place to meet their biological needs. . In Islam, the Qur'an has generally explained about communication within the family. This communication can be divided into three parts, namely communication between husband and wife, and communication between parents and children, as well as communication between siblings. If these three communications work effectively, then family integrity, harmony and happiness will be achieved